Diffusionless transformation of soft cubic superstructure from amorphous to simple cubic and body-centered cubic phases - Jie Liu (Nature Portfolio, 2021)
The arrangements of defect lines in liquid crystal blue phases provide promising templates for photonic crystals. Here Liu et al. investigate in detail how inter-phase transitions proceed, by intercepting nucleation with on-demand cross linking of a supporting polymer matrix.